2017
DOI: 10.1016/j.semnephrol.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

APOL1 Nephrotoxicity: What Does Ion Transport Have to Do With It?

Abstract: Summary Apolipoprotein L1 (APOL1) protein is the human serum factor that protect humans against Trypanosoma brucei brucei, the cause of trypanosomiasis. Sub species of T.b. brucei that cause human sleeping sickness —T b. gambiense and T.b. rhodesiense evolved molecular mechanisms that enabled them to evade killing by APOL1. Sequence changes (termed G1 and G2) in APOL1 gene that restored its ability to kill T.b. rhodesiense also increase risk of developing glomerular diseases and accelerate progression to end s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
(62 reference statements)
0
14
0
Order By: Relevance
“…The full‐length APOL1 wild‐type protein G0 has been subdivided into four domains: SP (1–27 AA), pore‐forming domain (PFD, 60–237 AA), membrane‐address domain (MAD, 238–303 AA), and serum resistance‐associated protein‐interacting domain (339–398) . We and others have reported that the PFD plays a critical role in APOL1 function .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The full‐length APOL1 wild‐type protein G0 has been subdivided into four domains: SP (1–27 AA), pore‐forming domain (PFD, 60–237 AA), membrane‐address domain (MAD, 238–303 AA), and serum resistance‐associated protein‐interacting domain (339–398) . We and others have reported that the PFD plays a critical role in APOL1 function .…”
Section: Introductionmentioning
confidence: 99%
“…However, in these models, comparative analysis of APOL1 risk and nonrisk proteins was not conducted. Nonetheless, the cellular expression of APOL1 risk variants has been shown to enhance K + efflux and activation of the mitogen‐activated protein kinase pathway in 293 T cells . Moreover, this effect of APOL1 risk alleles resulted in cytotoxicity, which was dose‐dependent .…”
Section: Introductionmentioning
confidence: 99%
“…APOL1 protein is known to form ion permeable pores in endosomal membranes of trypanosomes, allowing endosomal contents to leak into the cytoplasm and disrupt the molecular milieu [24]. Pore formation has also been reported to occur in HEK293 cells when APOL1 is over-expressed,[17] bolstering an emerging hypothesis that APOL1 -associated kidney damage may be due to toxic APOL1 -mediated pore formation [25]. However, previous investigations have yielded conflicting results with regard to risk-variant mediated disruption of ion concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies by the Pollak group indicate the role of potassium efflux in mammalian cytotoxicity as well [76, 77]. Exogenous expression of APOL1 using APOL1 cRNA injections in Xenopus oocytes increased ion permeability and induced morphological toxicity [78].…”
Section: Apol1-mediated Trypanosome Lysis and Renal Injury: Similar Mmentioning
confidence: 99%